Disruption of Ca2+i Homeostasis and Connexin 43 Hemichannel Function in the Right Ventricle Precedes Overt Arrhythmogenic Cardiomyopathy in Plakophilin-2–Deficient Mice. Issue 12 (17th September 2019) - Kim, Joon-Chul; Pérez-Hernández, Marta; Alvarado, Francisco J.; Maurya, Svetlana R.; Montnach, Jerome; Yin, Yandong; Zhang, Mingliang; Lin, Xianming; Vasquez, Carolina; Heguy, Adriana; Liang, Feng-Xia; Woo, Sun-Hee; et al.
Abstract : Background: Plakophilin-2 (PKP2) is classically defined as a desmosomal protein. Mutations in PKP2 associate with most cases of gene-positive arrhythmogenic right ventricular cardiomyopathy. A better understanding of PKP2 cardiac biology can help elucidate the mechanisms underlying arrhythmic and cardiomyopathic events consequent to PKP2 deficiency. Here, we sought to capture early molecular/cellular events that can act as nascent arrhythmic/cardiomyopathic substrates. Methods: We used multiple imaging, biochemical and high-resolution mass spectrometry methods to study functional/structural properties of cells/tissues derived from cardiomyocyte-specific, tamoxifen-activated, PKP2 knockout mice (PKP2cKO) 14 days post-tamoxifen injection, a time point preceding overt electrical or structural phenotypes. Myocytes from right or left ventricular free wall were studied separately. Results: Most properties of PKP2cKO left ventricular myocytes were not different from control; in contrast, PKP2cKO right ventricular (RV) myocytes showed increased amplitude and duration of Ca 2+ transients, increased Ca 2+ in the cytoplasm and sarcoplasmic reticulum, increased frequency of spontaneous Ca 2+ release events (sparks) even at comparable sarcoplasmic reticulum load, and dynamic Ca 2+ accumulation in mitochondria. We also observed early- and delayed-after transients in RV myocytes and heightened susceptibility to arrhythmias in Langendorff-perfused hearts. In addition, ryanodine receptor 2 in PKP2cKO-RV cells presented enhanced Ca 2+ sensitivity and preferential phosphorylation in a domain known to modulate Ca 2+ gating. RNAseq at 14 days post-tamoxifen showed no relevant difference in transcript abundance between RV and left ventricle, neither in control nor in PKP2cKO cells. Instead, we found an RV-predominant increase in membrane permeability that can permit Ca 2+ entry into the cell. Connexin 43 ablation mitigated the membrane permeability increase, accumulation of cytoplasmic Ca 2+, increased frequency of sparks and early stages of RV dysfunction. Connexin 43 hemichannel block with GAP19 normalized [Ca 2+ ]i homeostasis. Similarly, protein kinase C inhibition normalized spark frequency at comparable sarcoplasmic reticulum load levels. Conclusions: Loss of PKP2 creates an RV-predominant arrhythmogenic substrate (Ca 2+ dysregulation) that precedes the cardiomyopathy; this is, at least in part, mediated by a Connexin 43-dependent membrane conduit and repressed by protein kinase C inhibitors. Given that asymmetric Ca 2+ dysregulation precedes the cardiomyopathic stage, we speculate that abnormal Ca 2+ handling in RV myocytes can be a trigger for gross structural changes observed at a later stage. Abstract : Supplemental Digital Content is available in the text.